(untitled) (Research Nepal Journal of Development Studies, 2018)
Modern liberal economics is against the Buddhists economics. Unhealthy market competition, greed of money, top most professionalisms and economic depression and recessions are the dark side but reality of modern liberal economics. To avoid such negative consequences from livelihood, right livelihood, from a philosophy of noble eightfold path, Buddhists Economics will be a new dimension of new economic development. To check the current situation of Buddhists Economics in Nepalese Cooperatives and Agriculture a small literature review was conducted. From this review above specified hypothesis over the drawbacks of contemporary liberal economics have serious hegemony over small Nepalese Economy. Buddhists scholars must be able to impose the philosophy of Buddhists Economics in day to day life of people linked with business, production, cooperatives and agriculture.